Cooperativas agropecuárias frente à cadeia produtiva do biodiesel do Rio Grande do Sul: uma análise a partir do modelo linguístico SWOT-fuzzy - Wildner, Marluci Casalini (2016)
The biodiesel production chain in Rio Grande do Sul is based on the production of soybeans potential, traditional cultivation of family farmers. Agricultural cooperatives are important economic agents in the energy market. They hold about 30% of the receipt of the soybean crop, and are included in institutional actions foreseen by the National Plan for Production and Use of Biodiesel. Based on this reality, the objective of this research is to analyze the position taken by the agricultural cooperatives entered in the production chain of biodiesel soybean oil base in Rio Grande do Sul. Is employed multicases study method. The conceptual approach uses the SWOT and through the fuzzy sets, illustrating the positioning of the cooperative compared to production chain. The linguistic model was applied in five agricultural cooperatives, authorized by the Ministry of Agrarian Development to supply raw material to the biodiesel industry in the state. With the results of applying the SWOT-Fuzzy linguistic model, it was possible to explore the positioning of the cooperatives compered to the biodiesel production chain. Among the five analyzed cooperatives, the Coopermil has the boldest competitive positioning against the biodiesel chain, the internal environment is formed by intensity forces and the external environment predominance opportunity. The Cotrirosa has an internal organization with structured forces that allows positioning unobtrusively and capturing the opportunities in their favor and deflecting threats. The Cotribá and Cotrisal have an internal scenario classified as neutral, as the external environment is rooted in the development of potential opportunities with this characterization cooperatives adapt their forces and reduce their threats according to the opportunities that biodiesel chain offers. The cooperative with more discreet competitive positioning ahead the chain is Cotrijal that shapes their strengths and mitigates weaknesses in order to capture the biodiesel chain opportunity and divert the threat, the cooperative is positioned directly as the right time to market.